2005
DOI: 10.1590/s1413-86702005000600012
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA viral infection in Cuban Trichomonas vaginalis isolates

Abstract: Trichomonas vaginalis can be infected with double-stranded RNA (dsRNA) viruses designated T. vaginalis virus (TVV), which may have important implications for trichomonal virulence and disease pathogenesis. We tested for TVV in 40 fresh T. vaginalis isolates from Cuban patients by total extraction of nucleic acids (DNA and RNA). TVV was detected in 22 (55%) of the 40 T. vaginalis isolates. This gives an estimate of the infection rate of Cuban T. vaginalis isolates by the dsRNA virus. Future research should focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The high prevalence (43.5%) of TVVs found in this study is comparable to a prevalence of 55% (95% CI: 38.4–70.7) among Cuban isolates [ 36 ]. Two recent studies have reported lower carriage of TVV, 18.7% (95% CI: 11.5–28.0) in the Philippines [ 37 ] and 17.3% (95% CI: 7.8–31.4) among Iranian isolates [ 38 ], although the latter study only determined the presence of TVV1.…”
Section: Discussionsupporting
confidence: 65%
“…The high prevalence (43.5%) of TVVs found in this study is comparable to a prevalence of 55% (95% CI: 38.4–70.7) among Cuban isolates [ 36 ]. Two recent studies have reported lower carriage of TVV, 18.7% (95% CI: 11.5–28.0) in the Philippines [ 37 ] and 17.3% (95% CI: 7.8–31.4) among Iranian isolates [ 38 ], although the latter study only determined the presence of TVV1.…”
Section: Discussionsupporting
confidence: 65%
“…Nevertheless, in a study of adolescents with T. vaginalis infection, clinical symptoms e.g. vaginal discharge, dysuria, dyspareunia, and cervical erythema were significantly associated with TVV-positive status of the vaginal TV isolates, detectable by nucleic acids gel electrophoresis [50]. More efficient and cost-effective diagnostics and surrogate biomarkers are urgently needed for further clinical observational and interventional studies.…”
Section: Resultsmentioning
confidence: 99%
“…A few case studies comparing different aspects of trichomoniasis with the presence of TVV in T . vaginalis clinical isolates have noted correlations with patient signs and symptoms, but the case numbers have remained small (5, 13, 20). …”
Section: Introductionmentioning
confidence: 99%